2020
DOI: 10.3904/kjim.2019.097
|View full text |Cite
|
Sign up to set email alerts
|

What are the illnesses associated with frailty in community-dwelling older adults: the Korean Frailty and Aging Cohort Study

Abstract: Background/Aims: Frailty is mainly due to an age-related decrease in the physiological reserves needed to maintain biological homeostasis, but it can also occur as a result of chronic diseases. The purpose of this study was to identify illnesses associated with frailty in Korean community-dwelling older adults. Methods: This was a cross-sectional study that included 2,936 older adults aged between 70 and 84 years who had completed both interviews and physical function assessments for the Korean Frailty and Agi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…In acute care settings, performing comprehensive geriatric assessments (CGAs) for older patients is less feasible as CGAs frequently take > 30 minutes for a single patient. To address this unmet need, several screening measures of frailty for older adults have been developed and validated [11][12][13][14]. Among these instruments, the ones requiring physical performance assessments might be less applicable for acute hospital settings where patients experience sudden deconditioning due to acute illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…In acute care settings, performing comprehensive geriatric assessments (CGAs) for older patients is less feasible as CGAs frequently take > 30 minutes for a single patient. To address this unmet need, several screening measures of frailty for older adults have been developed and validated [11][12][13][14]. Among these instruments, the ones requiring physical performance assessments might be less applicable for acute hospital settings where patients experience sudden deconditioning due to acute illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…This could be due to lack of provision of proper healthcare resources to older adults with multiple comorbidities. Furthermore, Kim et al reported in their study that older Korean adults had about an average of 2.4 comorbidities, and that only certain diseases such as hypertension, diabetes, and arthritis were linked to frailty 27 .…”
Section: Discussionmentioning
confidence: 99%
“…15) The standardized CGA used for the FI can comprise assessments in Frailty is also known to be highly associated with hypertension, diabetes mellitus, cancer (other than minor skin cancers), chronic lung disease, heart attacks, congestive heart failure, angina, asthma, arthritis, stroke, and kid ney disease. 16,17) If frailty is caused by any disease, it is sometimes called secondary frailty. Otherwise, it is called primary frailty.…”
Section: Frailty Indexmentioning
confidence: 99%
“…Frailty is also known to be highly associated with hypertension, diabetes mellitus, cancer (other than minor skin cancers), chronic lung disease, heart attacks, congestive heart failure, angina, asthma, arthritis, stroke, and kidney disease [ 16 , 17 ].…”
Section: Diagnosis Of Frailtymentioning
confidence: 99%